Synthesis and Characterization of Zeolite-Encapsulated Copper(II) Complexes with Isomeric Benzoylpyridines - Ghansiala, Poonam (Asian Journal of Chemistry, 2011)
An attempt has been made to encapsulate copper(II) complexes of 2-, 3- and 4- benzoylpyridines in the cages of zeolite Y by flexible ligand method. These complexes are characterized by infrared, electronic and X-ray diffraction techniques. The data revealed that Cu2+ ion is in a pseudo tetrahedral environment in the cages of zeolite without any modification of the morphology and structure of zeolite.